Pengaruh Pemberdayaan Tenaga Kependidikan Terhadap Produktivitas Kerja (Studi Pada Tenaga Kependidikan di SLTA se-Kabupaten Tasikmalaya) - Asep Abdulah (Jurnal Pendidikan, Bahasa dan Budaya, 2023)
This study aims to determine and analyze the effect of empowering teaching staff on work productivity in high school education staff in Tasikmalaya Regency. The research method used in this study is a survey method. The population in this study were all high school education staff in Tasikmalaya Regency. Sampling from the study population was carried out using a total sampling technique, namely as many as 53 education staff. The analysis used is descriptive analysis and simple linear regression. The results of the study show that there is a significant effect of empowering teaching staff on work productivity in high schools throughout Tasikmalaya Regency. Empowerment of employees is an important strategy for organizations to increase the strength and engagement of their employees with the assumption that empowered employees tend to be more efficient in completing work. Thus, the Principal must maintain the empowerment that has been done before and increase empowerment in terms of credibility with employees such as involving employees in planning and decision-making processes.